Introduction to differential equations and dynamical systems - Williamson, Richard E. (McGraw-Hill, 1996)
The book integrates many of the classic ideas of differential equations and the more modern study of dynamical systems into an introductory course in differential equations. It also provides a variety of relevant applications of differential equations within framework of a traditional course